Alat Kebijakan dalam Sistem Pendidikan Sebagai Pilar untuk Kemajuan Pendidikan Nasional - Lili Raflika; Salniati Nasution; Khalid Samahangga (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Policy tools have an important role in shaping a quality, inclusive, and sustainable education system. This article aims to identify and analyze the various policy tools used in the education system, including regulations, economic instruments, and information instruments. Using an analytical-descriptive approach, this article explores how policy tools are applied to support the achievement of national education goals, such as improving access, quality, and equity in education. The findings show that the success of policy tools is greatly influenced by the effectiveness of implementation, the capacity of human resources, and synergies between various stakeholders. However, challenges such as access gaps in remote areas, technological limitations, and lack of transparency in policy management remain obstacles. To overcome these challenges, it is recommended that strategies in the form of strengthening human resource capacity, digitization of the education system, as well as increased collaboration between the government, the private sector, and the community. With the implementation of effective policy tools, the education system can become the main pillar in advancing the nation and creating a globally competitive generation.